2016
DOI: 10.1016/j.petrol.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optimization model for location and sizing of offshore platforms and location of oil wells

Abstract: a b s t r a c tThe oil field development is a hard and critical task that defines the main procedures to be performed during the oil field productive life. Given the complexity of this planning phase, methods to support decision making have been developed to assist in the proper application of high investments. This paper aims to report a 0-1 Linear Programming Model which minimizes the development costs of a given oil field as a whole. The model seeks to define: the number, location and capacities of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Piecewise reformulations of MINLPs have also been applied in many recent publications (Kosmidis et al, 2005;Gerogiorgis et al, 2009;Aguiar et al, 2012;Codas et al, 2012;Gunnerud et al, 2012;Silva and Camponogara, 2014). Rodrigues et al (2016) developed a new formulation called the Multicapacitated Platforms and Wells Location Problem (MPWLP) and solved it as an MILP using the CPLEX solver. The solution to this model provides the number and location of production platforms, wells and manifolds, the capacities of the production platforms, the interconnections between platforms, manifolds and wells, and which sections of each well should be vertical or horizontal.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Piecewise reformulations of MINLPs have also been applied in many recent publications (Kosmidis et al, 2005;Gerogiorgis et al, 2009;Aguiar et al, 2012;Codas et al, 2012;Gunnerud et al, 2012;Silva and Camponogara, 2014). Rodrigues et al (2016) developed a new formulation called the Multicapacitated Platforms and Wells Location Problem (MPWLP) and solved it as an MILP using the CPLEX solver. The solution to this model provides the number and location of production platforms, wells and manifolds, the capacities of the production platforms, the interconnections between platforms, manifolds and wells, and which sections of each well should be vertical or horizontal.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Many studies have investigated oil and gas network models that contain various types of facilities. Rodrigues et al [7] proposed a 0-1 programming model to determine the connections between FPSO units, manifolds, and facilities as well as the sizes and locations of platforms. In [8,9], the authors proposed a mixed integer linear programming (MILP) model to optimize the connections between wells and platforms while considering not only the installation time but also the linear drop of the reservoir pressure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section, scatter plots are presented in Figure 13 to show the well and MV (8,8,6,8,8,6) 46 (8,8,8,10,6,6) 48 (10,8,6,10,8,6) 40 (7,6,7,7,7,6) 42 (8,8,6,6,6,8) (5,6,6,6,5,5,6,5) 40 (5,5,5,5,5,5,5,5) 42 (6,5,5,6,5,5,…”
Section: Stability Of the Algorithmmentioning
confidence: 99%
“…Both papers concluded that the optimization layout problem can be described accurately by the presented mathematical models and the convergence rate of the given algorithms is efficient. Rodrigues et al (2016), in order to minimize the development costs of an oil field, proposed a binary linear programming that integrated interconnected decisions such as the number and location of wells and platforms, the location of manifolds, the well geometry and the production capacity of the platforms and its interconnection between manifolds and wells. Two case studies were proposed, and the results were consistent with reality.…”
Section: Introductionmentioning
confidence: 99%